16. Yüzyıl Şairlerinden Fazlî'nin "Gül ü Bülbül Mesnevisi"ndeki Şahıs Kadrosunun Tasavvufî Açıdan Değerlendirilmesi - Demirel, H.Gamze (Selcuk University, 2007)
Bu mesnevide “Gül ile Bülbül” arasında geçen aşk, tasavvufî açıdan ele alınmaktadır. Mesnevidekikahramanların her biri tabiat unsurları arasından seçilmiştir. Gül ile onun etrafındaşekillenen aşklar ve bu aşkların hangi boyutlarda (yüceltici, aşağılatıcı gibi) yaşandığınıngözler önüne serildiği hikayede Gül, benlik kaygısının ön plana çıktığı bir kişiliği temsil etmektedir.Bülbül’ün Gül’e olan aşkı ile bunun neticesindeki ruh haleti ise olayların esas yönünü belirler.

In this mesnevy, the love between “Gul u Bulbul” is taken up in a sufistic manner. Each of the characters in the mesnevy has been chosen from the ingredients of nature. In this story, in which loves –that are shaped around the rose- and the dimensions of them (exaltation, humiliation etc.) are expressed, the rose represents a character of having personality concern. The nightingale’s love towards the rose and its mood as a result of this love determines the main direction of the episodes.
A Sufictic Evaluation Of The Characters Of The Mesnevy “Gul u Bulbul” By Fâzlî 16th. Century Poet